The dynamic impact of low-cost carriers on full-service carriers and the tourism industry of South Korea: a competitive analysis using the Lotka–Volterra model. Issue 7 (3rd July 2018) - Khan, Nokhaiz Tariq; Kim, Yo Han; Kim, Yun Bae
ABSTRACT: The emergence of low-cost carriers (LCC) in the aviation industry has dramatically decreased the cost of short-to-medium distance air travel, alongside the growth of the tourism industry. LCC has also changed the competitive dynamics within the aviation industry, challenging the traditional market dominated by conventional full-service carriers. Past studies have demonstrated the scale of impact of LCC on the aviation market, but have yet to explore the intricate dynamics of competition in greater detail. This paper utilizes the Lotka–Volterra model to assess the changing impact of the entrance of LCC on South Korean tourism and airline industries. Our results offer insights to industry players on developing sustainable strategic plans for future routes and tourism destinations in Asia and beyond.